The Current Labor Policies of American Industries - Slichter, Sumner H. (Quarterly Journal of Economics, 1929)
I. The situation down to 1920. — The effects of pre-war immigration, 393. — The effects of the war, 395. — The failure of post-war changes in the labor market to end the interest of business men in industrial good will, 396. — II. The post-war dread of labor trouble, 398. — The inability or unwillingness of employers to reduce wages in proportion to the drop in wholesale prices, 400. — The better appreciation by managers of the relationship between morale and efficiency, 401. — III. The methods by which enterprises have attempted to make labor more efficient and more contented: Helping employees acquire property, 404. — Helping them acquire a "stake" in the business, 408. — Protecting the magainst arbitrary treatment, 411. — Rewarding continuity of service, 414. — Giving them opportunity to advance, 416. — Giving them security, 419. — Other methods, 421. — IV. The effect of the new personnel policies upon the present labor situation. — Their effect upon productivity per worker, 424 .— Their effect upon union membership, 426. — Their effect upon the number of industrial disputes, 428. — Their effect upon the rate of turnover, 429. — V. The effect of the new labor policies upon labor's bargaining power and upon the spread of unionism, 431.